Russian Steps On tour with the Royal Ballet's - Chapman, Deirdre (Dance Books Ltd., Alton,Hampshire (UK), 2003)
The Royal Ballet goes to Russia, a diary. PALABRAS CLAVE: Royal Ballet, Swan Lake, Mayerling, Tryst, Gloria, Moscow, June 2003.